PREVALENCE AND ASSOCIATED RISK FACTORS OF RENAL COMPLICATIONS IN CONGENITAL CARDIAC DISEASE PATIENTS - Khalil, Hafsa; Ahmed, Iftikhar; Saleem, Kamal; Younas, Umair; Iftikhar, Rawail; Khan, Adeela (Pakistan Armed Forces Medical Journal, 2018)
Objective: To investigate the risk factors associated with renal complications and comparison of peritoneal dialysis survival and non-survival patients after open heart surgery. Study Design: Descriptive cross-sectional study. Place and Duration of Study: Pediatric cardiac anesthesia Department of Armed Forced Institute of Cardiology & National Institute of Heart Diseases from Jul 2017 to Jan 2018. Material and Methods: Retrospective data was collected from hospital based registry. Demographics, clinical characteristics, complications and outcome of patients were recorded. Data analysis of 199 patients was done on SPSS version 22. Results: Total of 199 patients were enrolled in the study, mean age was 4.9 ± 5 years (p=0.01), 117 (59.1%) were male and 82 (40.9%) were female patients. Out of total, 24 (12%) patients had kidney disease (KD) and underwent peritoneal dialysis (PD). Sixteen children (66.7%) died after PD while 08 children (33.3%) survived after PD. 09 (37.5%) had pulmonary edema (p<0.001), 05 (20.8%) had pulmonary hypertension (p=0.005), 09 (37.5%) had high inotropic duration (p=0.004) and 13(54.2%) patients had low cardiac output (p=0.001). Conclusion: It was concluded that patients with renal impairment who underwent peritoneal dialysis had poor outcomes as they had longer hospital stay and high mortality rate. Risk factors associated with renal complications included pulmonary edema, high inotropic support, low cardiac output and pulmonary hypertension. Longitudinal follow-up studies with robust methodology are needed to fill significant knowledge gaps. There are currently no clear guidelines for clinicians in terms of renal assessment in the long term follow up after cardiac surgery in childhood.